Processo de mudança da cultura organizacional para a adoção de procedimentos cocriativos: um estudo de caso na multinacional GE Healthcare - Barbara, Bianca Zapparoli (2013)
This article seeks to identify the methods that can be used for cultural change in building a company cocreative, as well as obstacles faced in this process. The study analyzes the multinational GE Healthcare which gives the value creation overall strategy for ensuring greater access to the public health. As we used the theoretical model of strategic change Pettigrew, considerations of organizational culture Schein, Fleury and Deal and Kennedy, among others, and the four principles to Cocreate Prahalad and Ramaswamy. The method used was the case study, using the techniques of observation, analysis of internal and external content and half-structured opened interviews. The results indicated that the GE Healthcare Company owns an internal context that facilitated the use of a lot of mechanisms, due to its descentralized structure of power that enables a communication more efficient and also to have a culture opened for changes. The main challenge found by the organization was to provide a collaborative flow and to apply the new mindset between the administration and all cocriators inside the company